Scottish traveller tales : lives shaped through stories - Braid, Donald (University Press of Mississippi, 2002)
The "Travelling People" of Scotland are the traditionally nomadic minority group known also by the derogatory term "tinkers." Traveling in groups or in their individual caravans along the high roads and byways of Scotland, they have established a distinct identity and mode of life for themselves that preserves centuries-old cultural beliefs. For their skill as storytellers, as well as ballad singers, they are internationally recognized for the richest storytelling traditions of the world. One of their best-known storytellers is Duncan Williamson. He was fascinated by storytelling from an early